2011
DOI: 10.1002/anie.201007832
|View full text |Cite
|
Sign up to set email alerts
|

Coaxially Stacked Coronene Columns inside Single‐Walled Carbon Nanotubes

Abstract: Pancakes in tubes: Coronenes, a class of planar π‐conjugated molecules, organize in 1D structures when using single‐walled carbon nanotubes (SWCNTs) as templates (see picture). Coronene columns with coaxial stacking in SWCNTs exhibit characteristic fluorescence spectra that significantly differ from those of isolated coronene molecules and three‐dimensional crystals and that are related to their well‐ordered 1D structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
98
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 34 publications
(70 reference statements)
16
98
1
Order By: Relevance
“…No binding in calculation using GGA is also reported between noble gas atom and metal (22). Inclusion of van der Waals interaction can explain the preference of the molecule to align perpendicular to the tube axis (23), a result that is consistent with experimental results for stacked molecules inside CNT (24). We found that the preferable orientation of the acetylene molecule can be explained by using the Lennard-Jones potential.…”
Section: Methodssupporting
confidence: 78%
“…No binding in calculation using GGA is also reported between noble gas atom and metal (22). Inclusion of van der Waals interaction can explain the preference of the molecule to align perpendicular to the tube axis (23), a result that is consistent with experimental results for stacked molecules inside CNT (24). We found that the preferable orientation of the acetylene molecule can be explained by using the Lennard-Jones potential.…”
Section: Methodssupporting
confidence: 78%
“…[22] The emission spectrum in the range of 400-500 nm revealed signature of vibrational progression [23] and nearly holds mirrorimage relationship with the absorption bands (Figure 2 b) with a relatively small stokes shift, which is indicative of small structural relaxation in the excited state as one can expect for J-aggregation. [21] Relatively larger spectral width and stokes shift in the present case compared to classical example of J-aggregated cyanine dyes can be attributed to limited numbers of coherently coupled molecules as also observed for perylene dyes.…”
mentioning
confidence: 93%
“…The guest molecules in CNTs tend to possess a different conformation to that of their bulk phases. For instance, coronene, a typical aromatic molecule comprising 24 C atoms whose edges are completely terminated by H atoms, [16][17][18] forms a stacked structure inside CNTs in which the tilt angle of the molecule is shallower than that in their bulk herringbone structure. 18) Because of the formation of this hybrid structure, the electronic properties of both the CNT and coronene molecule are expected to be slightly different from those of isolated structures.…”
Section: Introductionmentioning
confidence: 99%